Surviving and thriving: male infertility through the lens of meta-ethnography - Fatemeh Abbasi; Mahla Talebi; Mohammadamin Jandaghian-Bidgoli; Negin Shaterian; Leila Dehghankar (Discover Social Science and Health)
Abstract Background Infertility in men is often overlooked, with limited focus on its emotional and psychological impact. This meta-ethnography reviews qualitative studies to explore how infertility affects men’s identities, emotions, and social lives. Methods The study followed Noblit and Hare's process for conducting a meta-ethnography, incorporating eMERGe Meta-Ethnography Reporting Guidelines. A purposeful sampling strategy was used, with a systematic search conducted across PubMed, ProQuest, MEDLINE, and Web of Science. Studies were selected based on their qualitative nature and focus on men’s experiences with infertility. Data were extracted independently by two authors, and analysis involved reciprocal translation of key themes, followed by an inductive synthesis to develop third-order constructs. Results Six key third-order construct emerged: Masculinity and Identity, Concealment of Infertility, Psychological and Emotional Impact, Social Isolation, Coping Mechanisms, and Rebuilding the Self. Infertility challenges traditional masculinity, causing emotional distress, isolation, and the use of coping strategies like avoidance and seeking support. Men often conceal their infertility due to stigma, but some rebuild their sense of self by redefining identity beyond fatherhood. Conclusion Male infertility has a profound emotional and social impact, influenced by societal norms around masculinity. A more inclusive approach to infertility care is needed, addressing both the medical and emotional aspects of men’s experiences.